The humane education of Waldorf - Attfield, Kate (Frontiers in Education, 2024)
In this Perspective paper I propose to explore the remarkable humanity-centred education designed by the Austrian philosopher Rudolf Steiner (1861 - 1925), along with his legacy in the form of the Waldorf schools that still serve children aged three to 18. Steiner was a polymath who could have been influenced by figures including the Roman playwright Terence, a freed slave who valued ‘humanity’, as well as the 16th Century humanist Erasmus of Rotterdam, who was in favour of humane education. International Waldorf education is now over 100 years old and Steiner’s focus on educating the human being in a healthy and integrated manner remains central. This paper provides an exploratory overview of Steiner-Waldorf education and offers a critical reflection on issues sometimes raised against its theory and practice. I have interviewed 43 Waldorf teachers from schools in Germany, the US and the UK covering their individual evaluation of human and humane-focused Waldorf pedagogy. The paper concludes that, given external government support, it can remain a visionary movement and a stimulus to other educational systems.